2009
DOI: 10.1111/j.1365-2486.2008.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in enzyme activities and temperature sensitivities in Arctic tundra soils

Abstract: Arctic soils contain large amounts of organic matter due to very slow rates of detritus decomposition. The first step in decomposition results from the activity of extracellular enzymes produced by soil microbes. We hypothesized that potential enzyme activities are low relative to the large stocks of organic matter in Arctic tundra soils, and that enzyme activity is low at in situ temperatures. We measured the potential activity of six hydrolytic enzymes at 4 and 20 1C on four sampling dates in tussock, intert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
194
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(221 citation statements)
references
References 33 publications
16
194
4
Order By: Relevance
“…The enzyme most sensitive to the temperature change was b-glucosidase (68-78% reduction with temperature decrease) and the least sensitive was urease (55-56% reduction). It has been observed in Alpine and Arctic tundra soils that C mineralization is more sensitive to low temperatures than N mineralization, which is a result of different sensitivities of the enzymes participating in the cycles of these elements (Koch et al 2007;Wallenstein et al 2009;2011;Jing et al 2014 …”
Section: Resultsmentioning
confidence: 99%
“…The enzyme most sensitive to the temperature change was b-glucosidase (68-78% reduction with temperature decrease) and the least sensitive was urease (55-56% reduction). It has been observed in Alpine and Arctic tundra soils that C mineralization is more sensitive to low temperatures than N mineralization, which is a result of different sensitivities of the enzymes participating in the cycles of these elements (Koch et al 2007;Wallenstein et al 2009;2011;Jing et al 2014 …”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported that increased temperature significantly alters microbial community structure and functioning by affecting substrate and nitrogen availability (Melillo et al, 2011;Bradford, 2013;Steinweg et al, 2013;DeAngelis et al, 2015). However, an understanding of microbial feedback to global warming remains limited, especially for the utilization of substrate and microbial activity associated with soil C cycling (Wallenstein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of different C-, N-, and P-degrading enzymes in soils is controlled by numerous factors including microbial biomass, community composition, substrate availability, microclimate, and stoichiometric demands 5,6 . However, in situ EEAs within the soil environment are also affected by temperature 7,8 , the binding of enzymes to soil clays and humic properties 18,19 . MUC-linked substrates are commonly associated with N-rich synthetic substrates such as proteins and/or amino acids.…”
Section: Introductionmentioning
confidence: 99%